PENGABDIAN KEPADA MASYARAKAT DONOR DARAH “APIKES BHJ MENEBAR MANFAAT, KITA SEHAT MEREKA SELAMAT” - Garis Gemilang; Hudiyati Agustini; Meliana (MEDICORDHIF Jurnal Rekam Medis, 2022)
Community Service is one of the Tri Dharma of Higher Education, namely education, research, and community service. One of the realizations of community service carried out by APIKES BHJ is in the form of blood donation which is carried out in a systematic and coordinated manner. Blood is one of the most important components in the body considering its function as a means of transportation. Lack of blood in the body can trigger a number of diseases starting from anemia, hypotension, heart attacks and several other diseases. To show concern for others, the entire APIKES Bhumi Husada Jakarta community held a Blood Donation activity with the theme "APIKES BHJ Spreads Benefits, We Are Healthy They Are Safe". The blood donation activity was held on Monday, March 22, 2021. Participants who attended on the day of the implementation were 36 people, consisting of 5 lecturers, 25 students, 4 employees, and 2 people from the general public. The number of participants who could donate blood was 22 people (61%), while 14 people (38%) could not donate blood, because of low hemoglobin or blood pressure, menstruating, and underweight. Keywords; PKM; blood donors;